Use of traditional medicine and control of hypertension in 12 Sub-Saharan African countries: the EIGHT cross-sectional study. (11th May 2022) - Lassale, C; Gaye, B; Diop, IB; Azizi, M; N'guetta, L; Antignac, M; Jouven, X
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): Camille Lassale is supported by a fellowship from "La Caixa" Foundation (ID 100010434). The fellowship code is LCF/BQ/PR21/11840003 Background: Use of traditional medicine (TM), is widespread in Sub-Saharan Africa as treatment option for a wide range of disease. We aimed to describe the profile of TM users and estimate the association with blood pressure (BP) and control of hypertension among hypertensive patients in a pan-African study. Methods: We included 2128 participants in the cross-sectional EIGHT study, who attended an outpatient consultation in the cardiology departments of 12 Sub-Saharan African countries (Benin, Cameroon, Congo, Democratic Republic of the Congo, Gabon, Guinea, Côte d'Ivoire, Mauritania, Mozambique, Niger, Senegal, Togo). We describe patients' characteristics according to TM use. We modelled the odds of uncontrolled hypertension, severe hypertension, and complications of hypertension by multivariable mixed logistic regression, and the linear association with systolic and diastolic BP by linear regression, all adjusted for age, sex, individual wealth index, adherence to hypertension conventional treatment, and country. Results: A total of 512 (24%) of participants reported using TM, and this percentage varied drastically across countries from 10% in the Congo to 48% in Guinea. TM users were more likely to be male, with poor treatment adherence, reporting missing treatment because it is too expensive, and presenting any complication of hypertension. TM use was associated with greater odds of hypertension (OR=1.30; 95% confidence interval: 0.99, 1.70), severe hypertension (OR=1.34; 1.04, 1.74) and of any complication of hypertension (OR=1.27; 1.01, 1.60), driven by renal complication (OR=1.57; 1.07, 2.29). Use of TM was associated with a 3.87 mmHg higher systolic BP and 1.75 mm Hg higher diastolic BP compared to no use. Conclusions: In this cross-sectional study of patients with hypertension in 12 Sub-Saharan African countries, we identified that the use of traditional medicine was associated with a poorer control of hypertension and more complications.